"Just like Any Other City": The De-Gasification of the Bhopal "Gas Relief" System - Hanna, Bridget (Social justice, 2014)
The article focuses on the gas relief hospital system employed in Bhopal, India after the Union Carbide pesticide plant disaster that killed 5,000 people due to the inhalation of methyl isocynate (MIC) gas in 1984. Topics include the health effects of the gas on survivors, the ongoing morbidity in Bhopal due to gas exposure, and hospital infrastructure in Bhopal.